Risk factors for tuberculosis in a low-income urban area of Cape Town, South Africa, with particular reference to the role of cannabis smoking - Jithoo, Anamika (Department of Public Health and Family Medicine, 2017)
Background: The association between Mycobacterium tuberculosis infection and tobacco smoking has recently been highlighted. The reason for this association remains unclear, but is postulated to result from the effects of smoking on pulmonary host defences. Cannabis impairs the immune function of alveolar macrophages and has been reported to increase susceptibility to respiratory infections. Aim: To examine risk factors for both Mycobacterium tuberculosis disease and infection, in particular the effects of cannabis smoking. Methods: A cross-sectional population survey of 3512 persons aged ≥15 years was performed in a predominantly low-income urban area of Cape Town, South Africa. Information on a history of tuberculosis and various risk factors including cannabis smoking was collected by means of an administered questionnaire. Ziehl-Neelson stained sputum smears were examined for acid fast bacilli and cultured on Lowenstein Jensen slants. Tuberculin skin testing (TST) was performed and an induration of ≥10mm read after 48-72 hours was considered positive. One joint year is defined as one joint per day for one year. Results: The prevalence of ever smoking cannabis was 11.3% (23% in men; 2.6% in women) and 6.4% were current smokers. A history of tuberculosis was reported by 9.7%; current disease confirmed in 1 %, and 76% had a positive TST. After adjusting for age, sex, tobacco smoking, income, education, occupational exposure, incarceration, alcohol use and body mass index, persons with a cumulative cannabis exposure of >70 joint years (approximately equivalent to 20 tobacco packyears) had an increased risk of past/current tuberculosis disease (OR 3.2; Cl:1.8 - 5.6). Cannabis joint years did not show an association with tuberculosis infection. Conclusions: This population study shows that cannabis smoking is positively associated with past/current tuberculosis disease, suggesting that cannabis may be a risk factor in the development of tuberculous disease.